2020
DOI: 10.1002/smll.202004400
|View full text |Cite
|
Sign up to set email alerts
|

Nanoglass–Nanocrystal Composite—a Novel Material Class for Enhanced Strength–Plasticity Synergy

Abstract: The properties of a material can be engineered by manipulating its atomic and chemical architecture. Nanoglasses which have been recently invented and comprise nanosized glassy particles separated by amorphous interfaces, have shown promising properties. A potential way to exploit the structural benefits of nanoglasses and of nanocrystalline materials is to optimize the composition to obtain crystals forming within the glassy particles. Here, a metastable Fe‐10 at% Sc nanoglass is synthesized. A complex hierar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…An interesting observation here is that the effect of Article chemical segregation is found to be negligible in both Pd-Si and Ni-P nanoglasses. Improved plasticity was also reported in Fe 90 Sc 10 nanocomposites where Fe nanocrystals were found to be distributed in the amorphous matrix [15]. Besides plasticity, significant variation of the yield strength was also reported in literature, with Cu-Zr and Sc 75 Fe 25 nanoglasses showing higher yield strength during nanoindentation, while Pd-Si and Ni-P showed lower yield strength during micro-pillar tests compared to their conventional amorphous counterparts [10,11,14,16].…”
Section: Introductionmentioning
confidence: 55%
See 2 more Smart Citations
“…An interesting observation here is that the effect of Article chemical segregation is found to be negligible in both Pd-Si and Ni-P nanoglasses. Improved plasticity was also reported in Fe 90 Sc 10 nanocomposites where Fe nanocrystals were found to be distributed in the amorphous matrix [15]. Besides plasticity, significant variation of the yield strength was also reported in literature, with Cu-Zr and Sc 75 Fe 25 nanoglasses showing higher yield strength during nanoindentation, while Pd-Si and Ni-P showed lower yield strength during micro-pillar tests compared to their conventional amorphous counterparts [10,11,14,16].…”
Section: Introductionmentioning
confidence: 55%
“…α-Fe is a by-product of the IGC synthesis because of the inherent difficulty in controlling the evaporation of the Fe-Sc alloy. From the characterization performed on the Fe-Sc nanocomposites, it was concluded that they are primarily composed of interfaces, cores and α-Fe crystallites [15]. Previous reports claimed that the segregation between core and interfaces is not very significant, only in the order of few atomic percent [23].…”
Section: Fe-sc Nanocompositesmentioning
confidence: 97%
See 1 more Smart Citation
“…An amorphous-crystalline oxidic nanocomposite surface layer (with a combination of high strength and high ductility) upon dry sliding has been achieved. The essential idea for this achievement is to use the high strength of metallic glass, while improving its homogeneous plastic deformability on surface by reducing deformation localization in shear bands (e.g., by introducing multiple shear bands) [1,177]. The coexistence of nanocrystal phase and amorphous phase helps achieve this goal, as shown in Fig.…”
Section: Tribological Designmentioning
confidence: 99%
“…With this motivation, Gleiter and coworkers (Jing et al, 1989;Gleiter, 2008;Gleiter, 2009;Gleiter, 2013;Gleiter, 2016) proposed the concept of nanoglasses (NGs) consisting of glassy grains (GGs) separated by glassy interfaces (GIs) of higher free volume, and later, several researchers have successfully fabricated NGs using different manufacturing routes (Gleiter et al, 2014;Nandam et al, 2017;Ivanisenko et al, 2018;Nandam et al, 2020). Extensive studies have been conducted on NGs to investigate their mechanical and functional properties using both experiments and simulations (Chen et al, 2011;Ritter et al, 2011;Sopu et al, 2011;Wang et al, 2011;Ritter and Albe, 2012;Adibi et al, 2013;Albe et al, 2013;Witte et al, 2013;Wang et al, 2014;Adjoud and Albe, 2016;Sniadecki et al, 2016;Nandam et al, 2017;Hirmukhe et al, 2019;Arnold et al, 2020;Singh et al, 2020a;Singh et al, 2020b;Hirmukhe et al, 2020;Katnagallu et al, 2020;Nandam et al, 2020). A series of MD simulation studies have been performed on NGs with different GG sizes and observed that the plasticity increases with the decreasing size of the GGs.…”
Section: Introductionmentioning
confidence: 99%